Effectiveness of qualified riflemen archery in control exercises with difficult conditions performance. - Antonov Sergej Vasil'evich; Pitin Mar'jan Petrovich (Kharkov National Pedagogical University, 2011)
In the article the study options adversarial exercise of archery with the abnormal conditions of a control to determine the specific training of athletes. It is found no differences between the absolute values of the results of the exercise of options sitting on a chair and standing on the platform and their difference from the values in the exercise with eyes closed. To set available of correlation relationships of varying strength between the results of the exercise of options sitting on a chair, standing on the platform with eyes closed, indicators of tension bow, qualifications and gender athletes.